The gender implications of Facebook pages and their role in prioritizing women issues - Zuhair Ibrahim Al - Salamy, Rand; Mwyt AlFaysa, Abd AlAmir (ALBAHITH ALALAMI, 2021)
Gender has considered and become a new trend in women’s studies, as it reflects the behaviors, roles and attitudes imposed by society on its members in accordance with their biological nature,with focusing on gender rather than on concentration on women, which is closely linked to the vision that concentrates on women’s problems which are not primarily according to their biological differences But rather to a greater extent to social, cultural, historical and religious barriers and Obstacles. Therefore, the qualitative division due to the concept of "gender" is not a rigid biological division, but is relied on the broad general context through which the social division of work is done. Thus, content in the pages of Facebook with high-level started to appear and calls for the need to cancel these roles and changing the other prevailing concepts. Thus , Gender disaggregation is therefore not a rigid biological division, but rather is based on the broad general context within which the social division of labor takes place. The contents of the Facebook pages, which are of a high level, call for the abolition of these roles and changing the prevailing concepts. The problem to the current research has summarized and raised by several questions like the main question that is concentrated on the Gender contents in Facebook Pages , as well as the influence of these contents in determining women’s priorities ? so , in order to answer on this question , there were several subdivided questions raised on the analytical and field level of research so as to reach the main objective that is represented with (the nature of the relationship between the gender implications on Facebook And women’s priorities(. The current researcher is belonged to the descriptive research the researcher has used , specifically the sample of surveying method so as to collect data and information on the relationship of the gender contents in the Facebook pages and in ranking of the priorities of the research sample, to depend on the questionnaire tool and the scale, as well. The researcher has depended and used the method of content analysis to analyze the gender contents of the selected sample Research relied on the analysis of the categories of what was mentioned recently to ?what was said ? How it was said? Through the construction of a special form for analysis. The researcher has reached to a number of results, the most important one , are: 1. Facebook is considered a means of mass communication that depends on the user in the extraction information and news, and it is considered , as well, a way to form direction and changing the behavior. 2. The relationship of gender contents in Facebook to women’s priorities is considered a positive one, ie, the more the number of content on a given topic the priority of women has increased